5.1 Ruptured membranes and risk of vertical transmission in women with HIV. (9th June 2014) - Townsend, C; Harding, K; Peters, H; De Ruiter, A; Francis, K; Taylor, G; Tookey, P
Abstract : Background: Most HIV-positive women on combination antiretroviral therapy (cART) with undetectable HIV viral load now deliver vaginally. Studies from the pre-cART era showed an association between duration of rupture of membranes (ROM) and mother-to-child transmission (MTCT). Here, we investigate the impact of ROM duration on MTCT rates in the cART era. Methods: The National Study of HIV in Pregnancy and Childhood collects data on all pregnancies in HIV-positive women in the UK and Ireland. We analysed singleton deliveries 2007–2012 in women receiving cART in pregnancy, excluding in utero transmissions. Results: ROM duration and infant's HIV status was available for 1973 pregnancies. The MTCT rate was 0.3% (6/1973), with no evidence of an association with ROM (≥4 vs <4 hours) overall, among term deliveries (≥37 weeks), or term deliveries with viral load <1000 copies/ml (Table ). There was only one transmission in 237 preterm deliveries; this was also the only transmission among the 97 deliveries where ROM was ≥24 h. Conclusions: This is the largest study to date to examine the effect of ROM on MTCT. The MTCT rate following ROM was low (0.3%), with no evidence of an association with duration of ROM.